The Importance of Classroom Interaction in Developing Student’s Speaking Abilities in EFL Classes Case of: First Year LMD Students of English at the University of Souk-Ahras - SELATNIA Bochra (My University, 2023)
ABSTRACT The research aims at investigating the importance of classroom interaction in enhancing EFL learners’ speaking competence, precisely the use of the two types of interaction that occur in the classroom: teacher-student interaction and student-student interaction in the Department of English Language at Mohamed Cherif Messaadia University, in Souk-Ahras. This exploratory, descriptive research utilized a mixed method to collect both quantitative and qualitative data as well as adopting three data collection tools. Initially, a questionnaire comprised of 19 questions was administered to eighty (80) students chosen randomly from the whole population (150) of first year students of English, Department of English, Souk-Ahras University. Secondly, an in-depth semi-structured interview was conducted with five EFL teachers of Oral Expression and Comprehension subject selected purposely. Finally, classroom observation was conducted with firs year students over six sessions during O E& C. The obtained findings unearthed that classroom interaction is very important, because of its value and significance in the pedagogical environment especially in the EFL setting, and the implementation of the types of classroom interaction will be very successful. Based on these results, the hypotheses are confirmed. ---------------- ملخص يهدف البحث إلى التحقق من أهمية التفاعل الصفي في تعزيز الكفاءة اللغوية لدى متعلمي اللغة الإنجليزية كلغة أجنبية، خاصة استخدام نوعي التفاعل الذي يحدث في الفصل الدراسي: التفاعل بين المعلم والطالب والتفاعل بين الطالب والطالب في قسم اللغة الإنجليزية. في جامعة محمد الشريف مساعدية في سوق أهراس. استخدم هذا البحث الاستكشافي الوصفي طريقة مختلطة لجمع البيانات الكمية والنوعية وكذلك اعتماد ثلاث أدوات لجمع البيانات. في البداية، تم إرسال استبيان يتكون من 19 سؤالًا إلى (80) طالبًا تم اختيارهم عشوائيًا من طلاب السنة الأولى(150)، قسم اللغة الإنجليزية، جامعة سوق أهراس. ثانيًا، تم إجراء مقابلة شبه منظمة متعمقة مع خمسة مدرسين للغة الإنجليزية كلغة أجنبية لموضوع التعبير الشفهي والفهم الذي تم اختيارهم عن قصد. أخيرًا، تم إجراء الملاحظة الصفية مع طلاب السنة الأولى على مدى ست جلسات خلال حصة التعبير الشفوي و الفهم. كشفت النتائج التي تم الحصول عليها أن التفاعل في الفصل الدراسي مهم جدًا نظرًا لقيمته وأهميته في البيئة التربوية خاصة في إعداد اللغة الإنجليزية كلغة أجنبية وتنفيذ أنواع سيكون التفاعل الصفي ناجحًا للغاية، وبناءً على هذه النتائج، تم تأكيد الفرضيات ---------------  RESUME La recherche vise à étudier l'importance de l'interaction en classe dans l'amélioration de la compétence orale des apprenants EFL, en particulier l'utilisation des deux types d'interaction qui se produisent en classe : l'interaction enseignant-élève et l'interaction élève-élève dans le Département de la langue anglaise à Université Mohamed Cherif Messaadia, à Souk-Ahras. Cette recherche descriptive exploratoire a utilisé une méthode mixte pour collecter des données quantitatives et qualitatives ainsi que l'adoption de trois outils de collecte de données. Initialement, un questionnaire composé de 19 questions a été administré à n80 étudiants choisis au hasard parmi N150 étudiants de première année d'anglais, Département d'anglais, Université Souk-Ahras. Deuxièmement, un entretien semi-structuré approfondi a été mené avec cinq enseignants EFL de matière d'expression et de compréhension orales sélectionnés à dessein. Enfin, une observation en classe a été menée auprès d'étudiants de première année sur six sessions d'expression et de compréhension orales. Les résultats obtenus ont révélé que l'interaction en classe est très importante en raison de sa valeur et de sa signification dans l'environnement pédagogique, en particulier dans le cadre de l'EFL, et la mise en œuvre des types d'interaction en classe seront très réussie. Sur la base de ces résultats. Les hypothèses sont confirmées.